International News Coverage in Malaysian and Ugandan Daily Newspapers - Adikata, Adnan Ali (1999)
Coverage of international news, represented in the newsworthiness determinants, news categories, and roles of the national, regional and international news agencies from a developing countries perspective, is an area that has not been thoroughly investigated. It was adopted wholly by the developing countries from the Western system with it's basic news standards. Hence, a need arose to undertake a study on international news coverage. The population was sampled by constructing weekly tables, which comprised of 1825 international news articles published between Jan 1st, 1996 and Dec 31st, 1998 by The Star (Malaysia) and The New Vision (Uganda) newspapers. Statistical procedures employing the Statistical Package for Social Sciences (SPSS) was used in data analysis. Specifically, descriptive statistics such as frequencies, percentages and chi-square were used. The finding indicate that the standard newsworthiness determinants were considered but at an alterable degree in determining the coverage of international news. It was also reported that news categories were substantial, however some categories were reported more than the others. The study also reveal that the national news agencies played a minimal role while the regional news agencies were found to be without any considerable role in international news coverage. Nevertheless, the international western news agencies played an overwhelmingly greater role in the coverage of international news. Reuters however, contributed much news than the AFP and AP towards international news coverage. The UPI on the other hand. did not provide any news story to the newspapers. The investigation suggests that the south-south cooperation concept exerted some considerable impact on the international news coverage. Hence, coverage of international news was based on the realisation of the concept.